2002
DOI: 10.1002/dc.10124
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of glucose transporter 1 and 3 in the placenta: Application to cytodiagnosis of Papanicolaou smear

Abstract: A positive immunostaining for glucose transporter 1 (GLUT1) was exclusively localized in microvilli on the free surface of syncytiotrophoblasts in the placenta. An enhanced immunoreaction for glucose transporter 3 (GLUT3) was elicited in the cell membrane of intermediate trophoblasts and cytotrophoblasts. Neither GLUT1 nor GLUT3 was positive in decidual cells and epithelial components from cervical dysplasia and carcinoma in situ. Cervicovaginal smears from six pregnant women containing atypical cells of unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…A finding of this study that may further explain variable expression of GLUT3 was the high degree of GLUT3 localization in the term placentalcytotrophoblast cells (CTBs). This is similar to the findings of multiple investigators who have observed GLUT3 expression exclusively in the CTBs of human placenta in early pregnancy [4345]. CTBs contain stem cells, which differentiate to become non-proliferative multinucleated STBs with cell fusion.…”
Section: Discussionsupporting
confidence: 91%
“…A finding of this study that may further explain variable expression of GLUT3 was the high degree of GLUT3 localization in the term placentalcytotrophoblast cells (CTBs). This is similar to the findings of multiple investigators who have observed GLUT3 expression exclusively in the CTBs of human placenta in early pregnancy [4345]. CTBs contain stem cells, which differentiate to become non-proliferative multinucleated STBs with cell fusion.…”
Section: Discussionsupporting
confidence: 91%
“…A finding of this study that may further explain variable expression of GLUT3 was the high degree of GLUT3 localization in the term placentalcytotrophoblast cells (CTBs). This is similar to the findings of multiple investigators who have observed GLUT3 expression exclusively in the CTBs of human placenta in early pregnancy [43][44][45]. CTBs contain stem cells, which differentiate to become non-proliferative multinucleated STBs with cell fusion.…”
Section: Discussionsupporting
confidence: 91%
“…Because other GLUTs were demonstrated to have expression in endometrium, [27][28][29][30] and because GLUT8 appeared to be hormonally regulated, 27,30,31 we hypothesized that GLUT1 and GLUT8 would be overexpressed in endometrial cancer compared to benign endometrial tissue, controlled for menopausal status. As with the upregulation of glucose transporters in other cancers, the upregulation of GLUT1 and GLUT8 may identify poorly differentiated, thus more aggressive endometrial tumors.…”
Section: Discussionmentioning
confidence: 99%